ESTIMATION RISK OF DEVELOPMENT OF INNATE VICES FACTORS ON A CITY BAKU - Сеідбекова Фатіма Октай кизи (World of Medicine and Biology, 2015)
Risk of development of innate vices factors were studied at 1070 pregnant, birth children with congenital development anomalies, that made a basic group. The control group consisted of 200 women who had children without congenital development anomalies. Found a link between closely related marriages between parents, the impact of infectious diseases on the development congenital anomalies. So at this rate CMV, the chance increases by 400 times (OR=400), when toxoplasmosis 260 times (OR=260) when herpes 158 times (OR=158), for chlamydia 90 times (OR=90) in acute respiratory viral infections in 16 times (OR=16) and the age of the parents up to 20 years and older than 35 years and some other factors.